Las TIC y su aplicación en el rendimiento académico de los estudiantes de octavo año paralelo B, de la escuela de Educación General Básica Dr. Daniel Rodas Bustamante, de la ciudad de Loja, periodo académico 2018-2019. Lineamientos Alternativos - Armijos Sanchez, Willan Alexander (2019)
The research was carried out in the School of EGB "Daniel Rodas Bustamante" whose general objective was to analyze the use of ICT and its application to improve the academic performance of students of eighth parallel year B, the school of Basic General Education Dr. Daniel Rodas Bustamante from the city of Loja, during the academic period 2018-2019. Where relevant issues are covered to what refers to the student's performance in the classroom and to base this research was made a descriptive study; using the methods: descriptive, observational, synthetic, inductive, deductive, hermeneutic and statistical; the techniques used were the interview and the survey, with its respective instrument: interview guide and questionnaire. In order to solve the misuse that students give to ICT, alternative guidelines have also been proposed with which it is expected to achieve results that favor the development of the 30 students of the 8th "B" and thus improve their academic performance , making good use and applying ICT in a responsible manner with the help of their parents and teacher. It is concluded that ICT is an important resource at present, this is because they generate significant learning in students, so its use requires a degree of responsibility on the part of both the teacher and the student, since at the time of being used erroneously could generate gaps in the teaching-learning process and therefore their academic performance will decrease significantly, so that the construction of alternative guidelines where students are the main beneficiaries is taken into account for this aspect